2017
DOI: 10.1007/s10683-017-9524-5
|View full text |Cite
|
Sign up to set email alerts
|

What if women earned more than their spouses? An experimental investigation of work-division in couples

Abstract: Female specialization on household work and male specialization on labor-market work is a widely observed phenomenon across time and countries. This absence of gender neutrality with respect to workdivision is known as the "work-division puzzle". Gender differences regarding characteristics (preferences, productivity) and context (wage rates, social norms) are generally recognized as competing explanations for this fact. We experimentally control for context and productivity to investigate preferences for work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
1
13
3
Order By: Relevance
“…11 Prior research on cooperation, using experiments, has found mixed results from a gender perspective, although recent evidence appears to point toward women being more cooperative than men, from a social dilemma perspective (Molina et al 2013). In the framework of the work-division within couples, research has found that there are gender differences in the contribution to the household Public Good (Thomas, 1990;Hoddinott and Haddad, 1995;Lundberg, Pollak and Wales, 1997;Cochard, Couprie and Hopfensitz, 2017), with a possible explanation being a greater sensitivity to social context by women (Ledyard 1995;Eckel and Grossman 2008;Croson and Gneezy 2009;Balliet et al, 2011).…”
Section: Empirical Strategy and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Prior research on cooperation, using experiments, has found mixed results from a gender perspective, although recent evidence appears to point toward women being more cooperative than men, from a social dilemma perspective (Molina et al 2013). In the framework of the work-division within couples, research has found that there are gender differences in the contribution to the household Public Good (Thomas, 1990;Hoddinott and Haddad, 1995;Lundberg, Pollak and Wales, 1997;Cochard, Couprie and Hopfensitz, 2017), with a possible explanation being a greater sensitivity to social context by women (Ledyard 1995;Eckel and Grossman 2008;Croson and Gneezy 2009;Balliet et al, 2011).…”
Section: Empirical Strategy and Resultsmentioning
confidence: 99%
“…Beblo and Beninger (2017) test in-couple income pooling in Germany, and find that income pooling, and thus cooperation, is more common among couples in which the spouses' socio-economic characteristics are more similar. Cochard, Couprie and Hopfensitz (2017) test for a willingness to cooperate and share income by men and women who are either in couple with each other or complete strangers, finding that lack of preferences for joint income maximization, having children, and being married lead to higher defection rates in the social dilemma. Dauphin, Fortin and Lacroix (2017) test the collective rationality (e.g., consumption efficiency) within households in Burkina Faso, using monogamous and polygamous households.…”
Section: Introductionmentioning
confidence: 99%
“…Second, though there has been growing interest in experiments that examine the decisions of married couples (e.g. Iversen et al (2010), Hoel (2015), Dasgupta and Mani (2015)) the role of production and the rules of entitlement in intra-household decisions has been largely neglected (though see Schröder et al (2013), Couprie et al (2015), Cochard et al (2018) and Aoyagi and Munro (2018) for a few, recent exceptions), despite the fact that, in many societies, production is a fundamental aspect of household livelihoods. Many of the pre-existing experiments using modified public good or dictator games and find that few households make decisions that are efficient.…”
Section: Introductionmentioning
confidence: 99%
“…1 I will start with a discussion of social emotions and how they influence behavior in interactions. I will then turn to four dimensions of increasingly precise information about the interaction partner: reputation, visual cues, talking to the other and finally knowing the other.…”
mentioning
confidence: 99%
“…The last chapter will conclude and introduce my ongoing research. 1 Parts of this document have been previously published in . 4 …”
mentioning
confidence: 99%